PENGARUH PROFITABILITAS, PERTUMBUHAN PENJUALAN, DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PERUSAHAAN LQ-45 DI BURSA EFEK INDONESIA) - Mila Setyani Purba; Cindy Claudia Br. Ginting; Kristi Endah Ndilosa Ginting; Debbi Chyntia Ovami (Fakultas Ekonomi Prodi Akuntansi, 2024)
The capital structure has a major influence on a company because it is part of the financial structure with reflects the comparison between long-term debt and equity seen from the asset side which includes the wealth structure and the liability side as a financial structure. The purpose lof lthis lstudy lwas lto ldetermine lthe leffect lof lprofitability, lsales lgrowth, lcompany lsize lon lstock lprices lwith lcapital ltructure las lan lintervening lvariable llisted lon lLQ-45 lon lthe lIndonesian lstock lexchange lfor lthe lperiod l2018 lto l2022. lThis lstudy lused la lquantitative lmethod lwith a population of 45 companies and 23 samples. Determination of the sample